(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
The elderly are a group vulnerable to dental and oral health problems due to decreased physiological function, the presence of comorbidities, and limitations in self-care. These conditions can increase the risk of oral infections that have the potential to develop into emergencies if not taken early preventative measures. In the Saribudolok area, there is still limited knowledge and awareness among the elderly regarding the importance of maintaining dental and oral health, so educational interventions that are applicable and easy to understand are needed. This community service activity was carried out in the Saribudolok Village, targeting 15 elderly people. The implementation method used a promotive-preventive approach through dental and oral health education integrated with simple health examinations as an initial screening for the risk of oral infection. Education was provided directly and interpersonally, accompanied by demonstrations of proper tooth brushing and denture care according to the elderly’s condition. Evaluation of the activity was conducted descriptively through observation of participant activity and a question and answer session to assess the elderly’s level of understanding after the education. The screening results showed that the majority of the elderly had dental and oral health problems that could potentially lead to oral infections. Based on the evaluation results, 60% of the elderly were in the low understanding category, 26.7% in the moderate category, and 13.3% in the high category. Elderly individuals with a high level of understanding were able to re-explain educational materials and practice proper oral care. This activity demonstrates that integrated oral health education with simple health check-ups can increase awareness among the elderly. However, a continuous educational approach is needed to optimize understanding as an effort to prevent oral infection emergencies.